Studies in law, politics, and society - Sarat, Austin (Studies in law, politics, and society, 2018)
Studies in Law, Politics, and Society provides a vehicle for the publication of scholarly articles in interdisciplinary legal scholarship. This volume features a special section with papers dedicated to law and disability. The chapters examine issues of HIV, obesity, disability rights, assisted suicide and prenatal testing.